Gut Microbiota and Their Role in Health and Metabolic Disease of Dairy Cow - Xu, Qingbiao; Qiao, Qinqin; Gao, Ya; Hou, Jinxiu; Hu, Mingyang; Du, Yufeng; Zhao, Ke; Li, Xiang (Frontiers in Nutrition, 2021)
Ruminants are mostly herbivorous animals that employ rumen fermentation for the digestion of feed materials, including dairy cow. Ruminants consume plant fibre as their regular diet but lack the machinery for their digestion. For this reason, ruminants maintain a symbiotic relation with microorganisms that are capable of producing enzymes to degrade plant polymers. Various species of microflora are hosted at distinct concentrations for accomplishing complete digestion, including bacteria, protozoa, fungi, archaea and bacteriophages. The ingested feed is digested at a defined stratum. The polysaccharic plant fibrils are degraded by cellulolytic bacteria and the substrate formed acted upon by other bacteria. This sequential degradative mechanism forms the base of complete digestion as well as energy harvesting from the ingested feed. The composition of microbiota readily gets tuned to the changes in the feed habits of dairy cow. The overall energy production as well as digestion is decided by the intactness of the resident communal flora. Disturbances in the homogeneity gastrointestinal microflora has severe effects on digestive system and various organs. This disharmony in communal relationship also causes various metabolic disorders. The role of symbiotic microflora in few important metabolic diseases occurrence and progress are discussed in this review. Future studies in multi-omics provides platform in determining the physiological and phenotypical upgradation of dairy cow for milk production.